KERJA SAMA INDONESIA-SWISS DALAM INDONESIA-EFTA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IE-CEPA) TAHUN 2018-2022 - Trisna Wahyuni; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes how international cooperation theory is applied in the cooperation between Indonesia and Switzerland in IE-CEPA 2018-2022. Switzerland is the largest economy in EFTA with a GDP share of 55%. Even so, Switzerland has a very large dependence on foreign trade. Indonesia and Switzerland have undergone a long bilateral relationship since 1952, but during this long period no trade agreement has been formed. Therefore, a cooperation mechanism is needed in terms of trade between Indonesia and Switzerland, which is contained IE-CEPA which has been going on since 2005. This study uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, and websites. This study uses the perspective of Neoliberalism and the theory of International Cooperation from K. J. Holsti and the Level of Analysis of Nations. The results of this paper identify the interests of Indonesia and Switzerland and the efficiency gained by the two countries in the IE-CEPA agreement. Switzerland and the EFTA countries prioritize how their superior products can be distributed massively, free of tariffs, and more competitive than European Union countries. Meanwhile, Indonesia is prioritizing how to find alternative markets for palm oil commodities. In addition, the IE-CEPA agreement provides efficiency for Indonesia-Switzerland's economic performance both in the trade of goods, services and even investment. Keywords: Political Economy, Comprehensive Economic Partnership Agreement, Switzerland.